2014
DOI: 10.1115/1.4028235
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Nacelles for Low Fan Pressure Ratio Propulsors

Abstract: As the propulsor fan pressure ratio (FPR) is decreased for improved fuel burn, reduced emissions and noise, the fan diameter grows and innovative nacelle concepts with short inlets are required to reduce their weight and drag. This paper addresses the uncharted inlet and nacelle design space for low-FPR propulsors where fan and nacelle are more closely coupled than in current turbofan engines. The paper presents an integrated fan-nacelle design framework, combining a splinebased inlet design tool with a fast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 23 publications
(43 reference statements)
2
70
0
Order By: Relevance
“…The size of the separation determines the distortion at the fan face which will influence the performance of the fan and its compatibility. studies can be broadly classified into the following categories, which explored the effect of the: (a) Off-design conditions like high-incidence and crosswinds on the intake-only configuration [1] and the hysteresis phenomena associated with flow separation and reattachment [2]; (b) Inlet distortion on the stability of the fan [3] ; (c) Fan-intake interaction on the incidence tolerance [4], [5] and the subsequent optimization of the intake shape [6].…”
Section: Fig 1: Schematic Showing the Flow Physics Around An Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The size of the separation determines the distortion at the fan face which will influence the performance of the fan and its compatibility. studies can be broadly classified into the following categories, which explored the effect of the: (a) Off-design conditions like high-incidence and crosswinds on the intake-only configuration [1] and the hysteresis phenomena associated with flow separation and reattachment [2]; (b) Inlet distortion on the stability of the fan [3] ; (c) Fan-intake interaction on the incidence tolerance [4], [5] and the subsequent optimization of the intake shape [6].…”
Section: Fig 1: Schematic Showing the Flow Physics Around An Intakementioning
confidence: 99%
“…It was shown that the fan stage is beneficial in increasing the tolerance to flow incidence and suppressing the flow distortion. Peter et al [6] presented an integrated fan-nacelle design framework based on CFD with the fan incorporated using a bulk body force model (BFM). A parametric study of the influence of intake-fan interaction on overall engine performance was conducted.…”
Section: Numerical Investigations Using Cfd (Computational Fluidmentioning
confidence: 99%
“…This improves propulsive efficiency; however, it comes with the negative trade off of larger and heavier nacelles. To combat this negative side effect, manufacturers are using shorter inlets with thinner nacelle lips [1]; however, these changes increase the chance of flow separation occurring in the inlet. The airframers' ability to determine the impact of these changes is important during design.…”
Section: Introductionmentioning
confidence: 99%
“…The airframers' ability to determine the impact of these changes is important during design. To model such situations, the airframer must be able to also model the engine fan stage as its operation will greatly impact the intake performance [1]; however, two major concerns arise while modelling these flows. The first is that it requires full wheel simulations to capture the non-uniform flow caused by inlet separation; using traditional bladed full wheel simulations to model non-uniform flow is very computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Modern engine architectures are trending towards higher bypass ratios and lower fan pressure ratios, which offer further improvements in propulsive efficiency with consequential reduction in emissions and noise. To circumvent the consequent increase in the weight and drag, engine manufacturers are exploring the possibility of employing shorter intakes and slimmer nacelle lips [1,2]. Such designs are however much more susceptible to flow separation due to the reduced diffusion capability of the intake, specifically under the off-design conditions of high crosswinds and high-incidence.…”
Section: Introductionmentioning
confidence: 99%